Uji Validitas dan Reliabilitas Pengukuran Kepuasan Pengguna RME dengan Metode EUCS - Saryadi Saryadi; Puguh Ika Listyorini; Liss Dyah Dewi Arini; Anggelli Marsha Pattinama (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to examine the validity and reliability of user satisfaction measurement for the Electronic Medical Record (EMR) system using the End User Computing Satisfaction (EUCS) approach. The five dimensions analyzed include content, accuracy, format, ease of use, and timeliness. Data were collected from 55 respondents, who were medical records staff at Dr. Moewardi General Hospital. The results show that all dimensions have Cronbach's Alpha values above 0.80, indicating a high level of reliability. The corrected item-total correlations also confirm strong construct validity. These findings demonstrate that the instrument used to measure user satisfaction with the EMR system is both valid and reliable, and can serve as a basis for continuous evaluation and development of health information systems.